Development and validation of a routine UV spectroscopic method for determination of camptothecin in cyclodextrin complexes, liposomes, niosomes, and solid dispersions in PEG 6000 - FATMI, Sofiane (Biopolymer Applications Journal, 2025)
A robust UV–Vis spectroscopic assay was developed and validated for quantifying camptothecin (CPT) in complex drug carriers, including cyclodextrin inclusion complexes, liposomal and niosomes suspensions, and PEG 6000 solid dispersions, addressing persistent analytical challenges posed by CPT’s poor solubility and labile lactone ring. The method exhibited exceptional linearity over 1–50 μg·mL⁻¹ (y = 0.0198 x + 0.0032, R² = 0.9991), specificity with no interference from excipients (102.17 % recovery; RSD = 0.85 %), and accuracy/precision meeting ICH Q2 criteria (mean recovery = 99.96 %; RSD < 2 %). The limit of detection (0.5 μg·mL⁻¹) and quantification (1.5 μg·mL⁻¹) enabled rapid (< 5 min) throughput without the need for costly HPLC columns or organic solvents, substantially reducing per-sample cost and environmental burden. This UV method not only surpasses many chromatographic techniques in speed and simplicity but also preserves the CPT lactone form by minimising exposure to aqueous neutral pH, thereby providing a reliable analytical tool for routine industrial quality control of advanced CPT formulations